9. Sendo, A = x - 2y B = 2x + y C = y + 3 Calcule: a) A + B / b) B - C / c) A . C
A) a) 8x -y / b) 12x - 10 / c) 9xy + 6x - 8y2 - 6y
B) a) x -y / b) 2x² - 3 / c) 12xy + 13x - 2y³ - 6y
C) a) 3x -y / b) 2x - 3 / c) xy + 3x - 2y² - 6y
D) a)6x -y / b) 4x - 3 / c) xy + 5x - 2y - 6y E) a) 3x / b) 2x / c) xy + 3x - 2x - 6y
Ajuda rápido quem poder :/
Respostas
respondido por:
1
Resposta:
a) x - 2y + 2x + y = 3x - y
b) 2x + y - y + 3 = 2x + 3
c) (x - 2y) . (y + 3) = - 2y² + xy + 3y - 6y = - 2y² + xy - 3y
Perguntas similares
3 anos atrás
3 anos atrás
3 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás